2021
DOI: 10.1253/circj.cj-20-1064
|View full text |Cite
|
Sign up to set email alerts
|

Value of Longitudinal Strain to Identify Wild-Type Transthyretin Amyloidosis in Patients With Aortic Stenosis

Abstract: Background: Wild-type transthyretin-related amyloidosis (ATTRwt) and degenerative aortic stenosis (AS) are both age-related. Diagnosis of cardiac amyloidosis (CA) among patients with AS may be difficult due to overlapping morphological and functional criteria. The aim of this study was to describe an echocardiographic longitudinal strain (LS) pattern among patients with AS with and without ATTRwt. Methods and Results:Patients who have AS with ATTRwt (n=30), AS without ATTRwt (n=50) and ATTRwt without AS (n=31)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…Anyway, the association of RASP with indexes of more severe valvular disease, related LV dysfunction and global heart repercussion, is in line with previous published data. 9,13 We further demonstrated that RASP in these patients with severe AS occurs in the absence of CA, which is accordance with what was demonstrated by Robin et al 21 1 and 2. *P-values after adjustment for atrial fibrillation, using parametric and non-parametric ANCOVA.…”
Section: Discussionsupporting
confidence: 91%
“…Anyway, the association of RASP with indexes of more severe valvular disease, related LV dysfunction and global heart repercussion, is in line with previous published data. 9,13 We further demonstrated that RASP in these patients with severe AS occurs in the absence of CA, which is accordance with what was demonstrated by Robin et al 21 1 and 2. *P-values after adjustment for atrial fibrillation, using parametric and non-parametric ANCOVA.…”
Section: Discussionsupporting
confidence: 91%
“…GLS impairment in ATTRwt-CA has a characteristic pattern called “apical sparing,” which refers to the relative reduction of the myocardial deformation of the basal segments compared with the apex ( 23 ). The coexistence of severe AS and ATTRwt-CA is associated with an early decrease of GLS: a value of −14% is sensitive but not specific for identifying ATTRwt-CA in patients with AS [area under the curve (AUC) 0.75] ( 24 ). Moreover, the apical sparing pattern is both sensitive and specific for the diagnosis of ATTRwt-CA in patients with increased left ventricular wall thickness ( 25 ).…”
Section: Echocardiographymentioning
confidence: 99%
“…The pattern apical sparing in patients with both AS and ATTRwt-CA has good accuracy (sensitivity 88%, specificity 68%, AUC 0.73) to diagnose ATTRwt-CA in patients with severe AS. Since the presence of apical sparing is common in AS even in the absence of ATTRwt-CA, it should be considered in combination with other echocardiographic parameters to raise the suspicion of ATTRwt-CA disease ( 24 ). On the other hand, AS is responsible for elevated wall stress and increased afterload that may mask the presence of apical sparing ( 10 , 26 ).…”
Section: Echocardiographymentioning
confidence: 99%
“…73 The classical appearance of cardiac amyloidosis without AS is a reduction in strain values at the basal to mid segments consistent with the progressive myocardial infiltration with "apical sparing" which is a specific pattern associated with cardiac amyloidosis. 74 However, a recent study by Robin et al 75 evaluating a sub-type of cardiac amyloid determined that an increase in GLS with apical sparing is common in AS patients even without the presence of amyloidosis. It is suspected that afterload mismatch attributed to AS conceals the typical apical sparing pattern, reducing the clinical usefulness of GLS at identifying cardiac amyloidosis until afterload is removed following intervention.…”
Section: Global Longitudinal Strain In Aortic Stenosismentioning
confidence: 99%
“… 74 However, a recent study by Robin et al. 75 evaluating a sub‐type of cardiac amyloid determined that an increase in GLS with apical sparing is common in AS patients even without the presence of amyloidosis. It is suspected that afterload mismatch attributed to AS conceals the typical apical sparing pattern, reducing the clinical usefulness of GLS at identifying cardiac amyloidosis until afterload is removed following intervention.…”
Section: Quantification Of Myocardial Motion: Tissue Doppler and Defo...mentioning
confidence: 99%